초음파 주파수분석법에 의한 발전소 고온배관재료의 크리프손상 평가 - 정민화(Min-Hwa Chung); 이상국(Sang-Guk Lee) (Han-guk haeyang gonghak hoeji (Online), 1999)
Boiler high-temperature pipelines such as main steam pipe, header and steam drum in fossil power plants are degraded by creep damage due to severe operationg conditions like high temperature and high pressure for an extended period time. Such material degradation lead to various component faliures causing serious accidents at the plant. Conventional measurement techniques such as replica method, electric resistance method, and hardness test method have such disadvantages as complex preparation and measurement procedures, too many control parameters, and therefore, low practicality and they were applied only to component surfaces with good accessibility. In this study, both artificial creep degradation test using life prediction formula and frequency analysis by ultrasonic tests for their preparing creep degraded specimens have been carried out for the purpose of nondestructive evaluation for creep damage which can occur in high-temperature pipelline of fossil power plant. As a result of ultrasonic tests for crept specimens, we confirmed that the high frequency side spectra decrease and central frequency components shift to low frequency bans, and bandwiths decrease as increasing creep damage in backwall echoes.